Implementation Of The Dick And Carey Model In Improving Islamic Religious Education Learning At Assalam Middle School Bandung (Qur'anic Inspiration Material In Preserving Nature) - Nugraha, Mulyawan Safwandy; Qodriani, Siti Hanna; Dedih, Ujang (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
Students have an unfavorable perception of Islamic Religious Education as an academic subject taught in institutions. Islamic Religious Education is often associated with the notion that these lessons consist mainly of boring lecture-based teaching. The lecture approach, consisting mostly of verses from the Koran and Hadith in Arabic, often prevents students from actively participating in the lesson material. Therefore, researchers attempt to eliminate this negative connotation by applying the Dick and Carey model in the context of Islamic Religious Education, with special emphasis on the subject of "Al-Quran Inspiration for Environmental Conservation." This research aims to evaluate the effectiveness of implementing the Dick and Carey Model in the context of learning Islamic Religious Education at the Middle School level. The Dick and Carey model was chosen because it is considered to be able to improve the current Islamic Religious Education learning model through ten methodical stages designed to improve the quality of learning in the classroom. The model mentioned above shows methodical attributes, which include the stages of developing learning outcomes, implementation, evaluation, and maintenance. This research uses a qualitative research approach, collecting information through interviews and observations. The research results show that the application of the Dick and Carey model effectively improves the quality of Islamic Religious Education learning, especially regarding "Quranic Inspiration for Environmental Conservation." The results of this research provide positive implications for the development of Islamic Religious Education learning strategies in junior high schools. The Dick and Carey model can be used as a reference for educators to design more structured and effective learning plans, by adapting the stages of the model to the context of religious education. This research contributes to efforts to improve the quality of Islamic religious education in formal education environments.   Keywords: Dick and Carey, Learning Model, Islamic Education